Optimization of MBR Field Integrated Production Model - Rizky Rezha Fauzi; Djoko Sulistyanto; Ghanima Yasmaniar (PETRO: Jurnal Ilmiah Teknik Perminyakan, 2020)
MBR Field is an onshore field located at East Kalimantan. In this field, there are five clusters with 2 main stations and 1 supporting station. With the current pipe flow conditions, this field has several constraints which are ESP maximum motor loads, ESP maximum frequencies, and current maximum water injection plant capacity. First, modeling is done with deviations of less than 10 percent to reach matching conditions in several parameters such as upstream pressure, downstream pressure, liquid rate, water rate, oil rate, and gas rate. Afterward, the first optimization is done by increasing the ESP frequency, increasing choke bean size, and shutting-in relatively low oil production wells with high water cut. But due to the water production is almost exceeding the water injection plant capacity, then the second optimization is done. The second optimization is done by increasing choke bean size and shutting-in relatively low oil production wells with high water cut. Each optimization is then followed by an analysis of pressure and flowrates alterations and the existence of backpressure in unoptimized wells.